2013
DOI: 10.3139/120.110511
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Effects on Fatigue Behaviour of a Forged Medium Carbon Microalloyed Steel

Abstract: The effect of different microstructures on the fatigue behaviour of a medium carbon vanadium microalloyed steel has been studied. Specimens were subjected to a controlled closed die forging followed by cooling in sand, air or oil, respectively. The hardness and fatigue properties of the microalloyed steel are determined and compared with those of ferrite-pearlite and martensite microstructures obtained by cooling with different mediums after forging. Relatively fine ferrite and pearlite increase the fatigue st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…However, most of these studies were focused on the effects of forging conditions on the microstructure and mechanical properties of MA steels [6][7][8]10,[22][23][24][25], only a few focused on the effects on fatigue properties [14,15,17,20,21]. For example, Gündüz et al studied the effect of different microstructures, which were obtained through post-forging controlled cooling, on the fatigue behavior of MA steel 38MnVS6 and showed that cooling rate had a remarkable effect on the microstructure, hardness and fatigue behavior [20]. Sankaran et al developed a multiphase microstructure in a V-bearing medium-carbon MA steel using a two-step cooling and annealing treatment following finish forging in an attempt to improve fatigue resistance [14,15,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of these studies were focused on the effects of forging conditions on the microstructure and mechanical properties of MA steels [6][7][8]10,[22][23][24][25], only a few focused on the effects on fatigue properties [14,15,17,20,21]. For example, Gündüz et al studied the effect of different microstructures, which were obtained through post-forging controlled cooling, on the fatigue behavior of MA steel 38MnVS6 and showed that cooling rate had a remarkable effect on the microstructure, hardness and fatigue behavior [20]. Sankaran et al developed a multiphase microstructure in a V-bearing medium-carbon MA steel using a two-step cooling and annealing treatment following finish forging in an attempt to improve fatigue resistance [14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…The forging parameters such as preheating temperature, soaking time, start and finish forging temperatures, strain (or degree of upset) utilized and the post-forging cooling rate as well as compositions of MA steel could highly influence on the microstructure and therefore play an important role on its final mechanical properties [6][7][8]10,14,15,17,20,[22][23][24][25]. However, most of these studies were focused on the effects of forging conditions on the microstructure and mechanical properties of MA steels [6][7][8]10,[22][23][24][25], only a few focused on the effects on fatigue properties [14,15,17,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the need for vehicles' weight reduction leads increasing demands for increasing strength, especially for increasing fatigue strength, of MA medium carbon steels. Therefore, increasing attentions have also been paid to fatigue fracture behavior of MA medium carbon steels for a proper selection or replacement of materials besides strength and toughness [2,[13][14][15][16][17][18][19][20]. Moreover, many actual forged components contain inevitable geometrical slight discontinuities or generally term of notches, which could generate local stress and strain concentrations in the notch area when are loaded.…”
Section: Introductionmentioning
confidence: 99%
“…A higher cooling rate leads to a finer microstructure and, therefore, to a higher strength. 7,8 Hajisafari et al 6 report on an optimum cooling rate of 3.8 K/s for effective precipitation hardening. At either lower cooling rate or higher cooling rate, the strength of the steel decreases.…”
Section: Introductionmentioning
confidence: 99%